Extracellular Vesicles in pregnancy: Their potential role as a liquid biopsy. (December 2022) - Buca, Danilo; D'Antonio, Francesco; Buca, Davide; Di Sebastiano, Francesca; Simeone, Pasquale; Di Girolamo, Raffaella; Bologna, Giuseppina; Vespa, Simone; Catitti, Giulia; Liberati, Marco; Miscia, Sebastiano; Lanuti, Paola
Abstract: Objective: Extracellular Vesicles (EVs) are cell-derived particles released during different pathophysiological processes, circulating in many body fluids and mediating the inter-cellular crosstalk. We have analyzed, for the first time, different EV phenotypes and concentrations in the peripheral blood of uncomplicated pregnant women. Study design: In this prospective case-control study, uncomplicated singleton pregnant women at term (N = 59) and aged matched non-pregnant women (N = 21) were enrolled. Freshly drowned peripheral blood samples were stained for flow cytometry analyses of EVs. Results: EVs derived from platelets, leukocytes, endothelial and epithelial cells were identified and counted. Platelet-derived EVs were higher in pregnant compared to non-pregnant women, both in terms of absolute counts (2064.4 ± 1156.3 vs 701.1 ± 378.8; p < 0.0001) and percentages (27.6 ± 17.2 vs 10.7 ± 5.9; p < 0.0001). The opposite pattern was observed both for concentrations of endothelial-EV counts (525.8 ± 499.6 vs 844.7 ± 652.9; p = 0.007) and percentages (6.1 ± 5.5 vs 11.8 ± 8.0; p < 0.0001) and leukocyte-derived EV percentages (10.2 ± 7.4 vs 17.9 ± 11.2; p = 0.002) EVs. Conclusions: Uncomplicated pregnancies are characterized by a specific EV signature. These cell-derived particles may therefore represent promising biomarkers of different pathological conditions complicating pregnancies, such as preeclampsia or preterm birth. Highlights: The primary aim was to describe the different EV phenotypes and concentrations in peripheral blood of uncomplicated pregnant women. Prospective case-control study including uncomplicated singleton pregnant women at term and aged matched non-pregnant women. Platelet-derived EVs were higher in pregnant compared to non-pregnant women, both in terms of absolute counts and percentage. EV concentration has a different pattern in pregnant compared to non-pregnant women.